Non-Verbal Pain Assessment: A Literature Review - AA, Che Badariah; H, Shamsul Kamalrujan (IIUM Medical Journal Malaysia, 2010)
Pain is influenced by multiple factors including personal experience, psychological, sociocultural and situational factors. Failure to recognise pain will lead to poor patient management and deleterious effect on the patients’ wellbeing. Assessing pain in paediatric and cognitively compromised patients remains a challenge. Pain assessment in these groups of patients depends on the observers’ assessment and studies have shown the discrepancy between the observers’ assessment and patients’ verbal report. A specific and accurate tool is required to assist in the pain assessment. Although there are assessment tools available using behaviour scoring system and physiological indicators, none of the tool demonstrates its superiority than the others. Biochemical indicators such as stress hormones are frequently measured and used in con-junction with verbal reports; however they are non specific to pain and are increased in inflammation, haemodynamic and emotional changes. The association between immunological indicators e.g. IL-1 , IL-6, IL- 8 and clinical pain has been shown, however; the definite correlation of the changes in the indicators and the level of pain is still unclear and may require further investigation.